Cultivation of Chlorella vulgaris JSC-6 with swine wastewater for simultaneous nutrient/COD removal and carbohydrate production. (December 2015) - Wang, Yue; Guo, Wanqian; Yen, Hong-Wei; Ho, Shih-Hsin; Lo, Yung-Chung; Cheng, Chieh-Lun; Ren, Nanqi; Chang, Jo-Shu
Highlights: A carbohydrate-rich microalga was grown on swine wastewater without anaerobic digestion treatment. Wastewater dilution ratio affected microalgal growth and wastewater treatment. High COD and nutrients removal was achieved during the microalgal growth. The EOMs were detected during the microalgae-based wastewater treatment. Abstract: Swine wastewater, containing a high concentration of COD and ammonia nitrogen, is suitable for the growth of microalgae, leading to simultaneous COD/nutrients removal from the wastewater. In this study, an isolated carbohydrate-rich microalga Chlorella vulgaris JSC-6 was adopted to perform swine wastewater treatment. Nearly 60–70% COD removal and 40–90% NH3 -N removal was achieved in the mixotrophic and heterotrophic culture, depending on the dilution ratio of the wastewater, while the highest removal percentage was obtained with 20-fold diluted wastewater. Mixotrophic cultivation by using fivefold diluted wastewater resulted in the highest biomass concentration of 3.96 g/L. The carbohydrate content of the microalga grown on the wastewater can reach up to 58% (per dry weight). The results indicated that the microalgae-based wastewater treatment can efficiently reduce the nutrients and COD level, and the resulting microalgal biomass had high carbohydrate content, thereby having potential applications for the fermentative production of biofuels or chemicals.